ISU-ISU TENTANG KANONISASI DAN HUBUNGANNYA DENGAN KEWIBAWAAN ALKITAB - vinus zai (Sekolah Tinggi Teologi Imauel Pacet, 2022)
AbstractWe know that the issue of canonization is often used as a hot topic of discussion in theological schools, churches and also becomes the subject of attacks against Christianity by people outside of Christianity. Often raises the question of how the canon was actually formed, which is of deep concern in the canon, namely the arrangement of the books of the Old Testament as well as the New Testament. Many consider that the formation of the canon is the result of human choices and decisions. And the next attack, if it is a human choice and decision, the authority of the Bible as the Word of God needs to be questioned. In addition to the arrangement of the books in the Bible and their authority, another issue that is often a topic of discussion or debate among Christians and non-Christians is what is the standard in determining the canon? What is canon for canon?Before we understand the issue that is the topic of discussion or debate above, we first need to understand and understand the term canon that was raised in Christianity from the first century to the second century so thatKeywords: Canonization, canon terms Abstrak Kita mengetahui bahwa Isu kanonisasi seringkali dijadikan sebagai bahan diskusi yang hangat di sekolah-sekolah Teologi, gereja dan juga menjadi bahan serangan tehadap kekristenan oleh orang-orang di luar kristen. Sering kali memunculkan pertanyaan tentang bagaimana sebenarnya terbentuknya kanon, yang menjadi perhatian mendalam dalam kanon yaitu susunan kitab-kitab Perjanjian Lama dan juga Perjanjian Baru. Banyak pihak menganggap bahwa pembentukan kanon merupakan hasil pilihan dan keputusan manusia. Dan yang menjadi serangan selanjutnya kalau memang itu pilihan dan keputusan manusia kewibawaan Alkitab sebagai Firman Allah perlu dipertanyakan. Selain penyusunan kitab-kitab dalam Alkitab dan kewibawaannya, isu lain yang seringkali menjadi topik pembicaraan atau perdebatan dikalangan Kristen dan Non Kristen yaitu Apa yang menjadi ukuran dalam menentukan kanon? Apa kanon bagi kanon? Kata Kunci: Kanonisasi, istilah kanon